Respuesta :

Answer: x² - (3/4)x + 9/64 = (x + 3/8

Step-by-step explanation:

Concept:

Here, we need to know the idea of completing the square.

Completing the square is a technique for converting a quadratic polynomial of the form ax²+bx+c to the form (x-h)²for some values of h.

If you are still confused, please refer to the attachment below for a graphical explanation.

Solve:

If we expand (x - h)² = x² - 2 · x · h + h²

Given equation:

  • x² - (3/4)x +___ = (x - __)²

Since [x² - (3/4)x +___] is the expanded form of (x - h)², then (-3/4)x must be equal to 2 · x · h. Thus, we would be able to find the value of h.

  • (-3/4) x = 2 · x · h ⇔ Given
  • -3/4 = 2 · h ⇔ Eliminate x
  • h = -3/8 ⇔ Divide 2 on both sides

Finally, we plug the final value back to the equation.

  • x² - 2 · x · h + h² = (x - h)²
  • x² - (3/4)x + (-3/8)² = (x + 3/8)²
  • x² - (3/4)x + 9/64 = (x + 3/8

Hope this helps!! :)

Please let me know if you have any questions

Ver imagen eunice1234
ACCESS MORE